A walk in the woods : the world's funniest travel writer takes a hike - Bryson, Bill (Black Swan, 2015)
Bryson gets the idea to hike the Appalachian Trail shortly after moving to Hanover, New Hampshire, when he stumbles onto part of the trail on a short hike near his home. He has no real wilderness experience, so he asks around and reads up on the trail, discovering that the perils awaiting him include snakebites, bear attacks, poison ivy, flooding rivers, and a long list of injuries and diseases he might fall victim to. To prepare, Bryson heads to his town's sporting goods store and spends an afternoon with Dave Mengle, who he has been told is a local expert on the Trail. Mengle presents him with a barrage of choices of packs, sleeping bags, cook sets, boots, tents, and thermal clothing. Bryson spends a small fortune and is left wondering what he's gotten himself into.